2020
DOI: 10.1002/rcm.8747
|View full text |Cite
|
Sign up to set email alerts
|

Fiber spray ionization mass spectrometry in forensic chemistry: A screening of drugs of abuse and direct determination of cocaine in urine

Abstract: Rationale Ambient mass spectrometry techniques are much required in forensic chemistry to evaluate evidence with low analytical interference, high confidence, and accuracy. However, traditional methodologies, such as paper spray ionization, have been shown to present low sensitivity in the analysis of illicit drugs from biological matrices. Methods Fiber spray ionization mass spectrometry (FSI‐MS) was developed using a capillary polypropylene (PP) hollow fiber. Seized samples of drugs, i.e. a tablet, blotter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…The value of magnetic moment of Fe(III) complex was 5.30 B.M., which equivalent to an octahedral geometry of five unpaired electrons in the Fe(III) ion. [ 60–62 ] Also, the octahedral geometry of the Co(II) complex was confirmed by its magnetic moment (5.08 B.M.). [ 63,64 ] Co(II) complex had three bands in its spectrum at 14,444, 24,845, and 27,920 cm −1 , which referred to the 4 T 1g (F) → 4 T 2g (F) ( v 1 ); 4 T 1g (F) → 4 A 2g (F) ( v 2 ); and 4 T 1g (F) → 4 T 1g (P) ( v 3 ) transitions, predictable for an octahedral structure.…”
Section: Resultsmentioning
confidence: 99%
“…The value of magnetic moment of Fe(III) complex was 5.30 B.M., which equivalent to an octahedral geometry of five unpaired electrons in the Fe(III) ion. [ 60–62 ] Also, the octahedral geometry of the Co(II) complex was confirmed by its magnetic moment (5.08 B.M.). [ 63,64 ] Co(II) complex had three bands in its spectrum at 14,444, 24,845, and 27,920 cm −1 , which referred to the 4 T 1g (F) → 4 T 2g (F) ( v 1 ); 4 T 1g (F) → 4 A 2g (F) ( v 2 ); and 4 T 1g (F) → 4 T 1g (P) ( v 3 ) transitions, predictable for an octahedral structure.…”
Section: Resultsmentioning
confidence: 99%
“…The technique was able to successfully detect both codeine and methadone in raw urine. Fiber spray ionization (FSI)‐MS has also been applied to the detection of cocaine in urine 72 . FSI utilized a capillary polypropylene hollow fiber, which was dipped directly into the lipid sample.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%
“…On the other hand, low-polarity analytes interact less with the cellulosic paper, which favors their elution while improving analyte ionization. Chemical modifications of the paper surface can help improve the efficiency of PSI and increase analyte-specific sensitivity (Damon et al, 2016;Filho et al, 2020;Rossini et al, 2020).…”
Section: Type Of Chemistrymentioning
confidence: 99%
“…On the other hand, in the PSI technique, powders are dissolved and spotted onto the substrate, and proteins and salts from blood and urine matrices bind well to the cellulosic paper, which prevents clogging at the spray tip and reduces background noise, allowing for LODs in the low picogram range to be achieved (Kennedy et al, 2018;Ma et al, 2015;Vandergrift et al, 2018). Nevertheless, a few matrix effects using PSI have also been reported and, as previously mentioned, the solvent choice has a greater impact on matrix effects than paper properties (Bills & Manicke, 2020;Bills et al, 2018;Bruno et al, 2017;Filho et al, 2020). As an example, observed up to 48% of interference in the lower limit of quantification (LLOQ) of amfetamine-like compounds in whole blood using PSI-MS; visual inspection revealed that these samples were extremely viscous and full of clots, potentially causing the interference .…”
Section: Sensitivitymentioning
confidence: 99%